"You out-gayed the gays": Gay aesthetic power and lesbian, bisexual, and queer women in LGBTQ spaces. Issue 3 (2nd July 2020) - Stone, Amy L.
Abstract: In lesbian, gay, bisexual, transgender, and queer (LGBTQ) spaces, gay male practices, sexualities, and priorities often dominate. I argue that in mixed-gender LGBTQ festival spaces in the South, gay aesthetics are normative, which often minimizes the contributions of lesbian, bisexual, and queer (LBQ) women. I compare two festival events run by the LGBTQ community—Cornyation, a mock debutante pageant that is part of Fiesta in San Antonio, Texas, and Osiris Ball, a formal Carnival ball during Mardi Gras in Mobile, Alabama. This research is based on participant observation data collected at both events over several years and 38 interviews conducted with event participants. I argue that at these events, gay aesthetic power is exerted through the expectation that LBQ women should master these aesthetics, a dynamic that often relies on gay men as arbiters of successful mastery. These processes were more dramatic in organizations and spaces where men were a numerical majority. This marginalization fits within a pattern of androcentric bias in both the arts and the workplace.